2022
DOI: 10.37897/rjn.2022.2.11
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of pain and comorbidities in geriatric subjects in Indonesia: A hospital-based national clinical survey

Abstract: Background. Pain is one of the most common health problems often experienced by the elderly. Research on pain and its comorbidities in elderly are crucial, because it relates to disability and impairment in quality of life. Unfortunately research related to pain in the elderly and co morbidities are still limited in Indonesia, better understanding about pain can be a vital consideration of treatment and drug consideration. This study was conducted to provide an overview of pain and its comorbidities in elderly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…[6] National prospective survey in Indonesia reported that from 8000 participants with pain complaints, 21% had at least 1 symptom of neuropathic pain. [1] Neuropathic pain has a diverse and large variety of underlying disease or lesion origins that are usually difficult to treat, such as trauma to the nervous system, vascular disease, nerve compression, infection disease, hereditary syndromes, metabolic disease, or neurological disease. [7] Because of its complexity, neuropathic pain is often challenging to diagnose and treat, thus leading to underdiagnosis and ineffective treatment by physicians.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[6] National prospective survey in Indonesia reported that from 8000 participants with pain complaints, 21% had at least 1 symptom of neuropathic pain. [1] Neuropathic pain has a diverse and large variety of underlying disease or lesion origins that are usually difficult to treat, such as trauma to the nervous system, vascular disease, nerve compression, infection disease, hereditary syndromes, metabolic disease, or neurological disease. [7] Because of its complexity, neuropathic pain is often challenging to diagnose and treat, thus leading to underdiagnosis and ineffective treatment by physicians.…”
Section: Discussionmentioning
confidence: 99%
“…[6] National prospective survey in Indonesia reported that from 8000 participants with pain complaints, 21% had at least 1 symptom of neuropathic pain. [1]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Di Indonesia prevalensi LBP belum diketahui secara pasti, namun LBP merupakan nyeri neuropatik yang paling sering ditemukan. 4 Penelitian menunjukkan bahwa prevalensi LBP pada populasi usia produktif di Jatinangor, Jawa Barat sebesar 38,4%. 5 Menurut World Health Organization (WHO) LBP termasuk dalam 10 besar gangguan penyebab penurunan kualitas hidup seseorang.…”
Section: Pendahuluanunclassified
“…Prevalensi LBP pada tahun 2017 diperkirakan sekitar 7,5% dari populasi global, atau sekitar 577,0 juta orang (Tamrakar et al, 2021). Sebuah studi di Indonesia menunjukkan bahwa prevalensi nyeri punggung bawah terdapat pada 21,8% dari 8.160 partisipan dari 13 kota di Indonesia (Purwata et al, 2015). Berdasarkan hasil penelitian yang dilakukan terhadap 270 mahasiswa kedokteran dan dokter magang di Faridpur Medical College, Bangladesh pada tahun 2020 didapatkan prevalensi kejadian LBP dalam 6 bulan adalah 46,9% (Sany et al, 2021).…”
unclassified